Optimizing Traumatic Limb Salvage: Ectopic Implantation and Staged Rotationplasty - Yi-Keng Hsieh; Chang-Heng Liu; Ching-Hsuan Hu (Medicina, 2023)
Rotationplasty, a limb-saving procedure involving a 180-degree ankle rotation to function as a knee joint, is now standard for treating distal femur osteosarcoma. However, challenges related to self-identification persist within the Asian population. This study presents a case involving the successful application of temporary ectopic implantation followed by staged rotationplasty after a severe traumatic amputation, resulting in a favorable outcome. Additionally, a systematic review is conducted to summarize the various difficulties and complications encountered in different studies. This approach improves the feasibility of rotationplasty in traumatic cases and enhances patient and family comprehension.